2006
DOI: 10.1159/000091391
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Calcium-Activated Chloride Channel 1 and MUC5AC in Goblet Cell Hyperplasia Induced by Interleukin-13 in Human Bronchial Epithelial Cells

Abstract: Background:Interleukin (IL)-13 has recently been reported as the major T-helper 2 cytokine involved in mucus overproduction and oversecretion in allergic airways. However, the relationship between human calcium-activated chloride channel-1 (hCLCA1) and MUC5AC induced by IL-13 in vitro has not been fully investigated. Objectives: The present study examines whether IL-13 induces the expression of hCLCA1 in normal human bronchial epithelial (NHBE) cells. We also investigated the relationship between hCLCA1 and MU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 59 publications
(60 reference statements)
2
46
0
Order By: Relevance
“…Expression of hCLCA1 or mCLCA3 was found to be up-regulated following exposure to respiratory tract irritants that are responsible for a Th2 local inflammation [26,34]. It has been shown that at transcript and protein level, expression of hCLCA1 was up-regulated by IL-13 in normal human bronchial epithelial cells in vitro [33]. Whether the secretion of the ovine CLCA protein has a direct or indirect function in worm expulsion remains unknown, although hCLCA1 has been associated with an increase in mucus production following a Th2 response of the respiratory tract [34].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of hCLCA1 or mCLCA3 was found to be up-regulated following exposure to respiratory tract irritants that are responsible for a Th2 local inflammation [26,34]. It has been shown that at transcript and protein level, expression of hCLCA1 was up-regulated by IL-13 in normal human bronchial epithelial cells in vitro [33]. Whether the secretion of the ovine CLCA protein has a direct or indirect function in worm expulsion remains unknown, although hCLCA1 has been associated with an increase in mucus production following a Th2 response of the respiratory tract [34].…”
Section: Discussionmentioning
confidence: 99%
“…IL-13 induces the cell proliferation and goblet cell hyperplasia of human airway epithelial cells in vitro [7,8]. We previously reported that IL-13 induced MUC5AC expression with the development of goblet cell hyperplasia in human bronchial epithelial cells [9].…”
Section: Introductionmentioning
confidence: 94%
“…We previously demonstrated that IL-13 induces goblet cell hyperplasia in human airway epithelial cells via IL-13Rα 1 [9], but the role of IL-13Rα 2 on the IL-13-induced goblet cell hyperplasia remains to be elucidated.…”
Section: Il-13 Exerts Its Biological Activities By Binding To Its Recmentioning
confidence: 99%
See 2 more Smart Citations